A comparative study of the effectiveness of ca-alginate and k-carrageenan beads as support material for enzyme immobilization - Razizad, Anis Nadzirah; Jameel, Ahmad Tariq (2015)
This research aimed to compare the effectiveness of Ca-alginate and K-carrageenan as support matrix for enzyme immobilization, especially with respect to having good retention of immobilized enzyme activity, multiple reusability and having superior maximum rate of reaction as well as ease of immobilization. Entrapment method was employed for the immobilization of beta-glucosidase enzyme in Ca-alginate and Kcarrageenan beads. The results were compared with those of free enzyme. This study aimed to fulfill three objectives: (1) to investigate the effect of design parameters on enzyme activity; (2) to determine the reusability of immobilized catalyst, and; (3) to evaluate the kinetic parameters of beta glucosidase immobilized on calcium alginate and potassium carrageenan beads. At a fixed substrate concentration, optimum pH and bead size for enzyme immobilization on Ca-alginate were 5 and 5 mm respectively, while for the K-carrageenan these were pH 4 and 5 mm bead size. The immobilized enzyme on Ca-alginate and K-carrageenan were found to follow Michaelis-Menten kinetics. Michaelis parameters Vmax and KM for Ca-alginate were found to be 65.36 mmol/min and 8.60 mM respectively, and for K-carrageenan 61.73 mmol/min and 0.94 mM respectively, while Michaelis constants for the free enzyme were 70.42 mmol/min and 2.71 mM. Higher Vmax value for free enzyme is due to the negligible mass transfer resistance to substrate diffusion to the enzyme active sites. For the residual activity after multiple uses, Ca-alginate retained the highest activity with 60.5 % of the initial activity and K-carrageenan retained only 6.83 %. K-carrageenan seems to have high affinity for the substrate while Ca-alginate has excellent stability. Keywords-glucosidase; K-carrageenan; Ca-alginate; Enzyme activity; Immobilization